2017
DOI: 10.1159/000478989
|View full text |Cite
|
Sign up to set email alerts
|

“Lanthanic Presentation” in First-Episode Psychosis Predicts Long Service Delay: The Challenge of Detecting Masked Psychosis

Abstract: Background/Aims: Studies of pathways to care in first-episode psychosis have documented a substantial treatment delay occurring after patients enter mental health services. An initial presentation with neurotic rather than psychotic symptoms is common in first-episode psychosis. The term “lanthanic patient” has been used to refer to patients presenting with a reason for help-seeking that is unrelated to the underlying pathology. The aim of this study is to explore whether a lanthanic presentation is related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…Our findings support earlier reports of a long diagnostic pathway to schizophrenia with depressive and negative symptoms and cognitive deficits before the emergence of psychotic symptoms. [69][70][71][72] We also found increased use of somatic health care services at least 5 years before index date, which is in line with earlier Danish studies of increased use of primary care 73 and somatic diseases before first diagnosis of schizophrenia. 74 The same pattern of increased societal costs was identified among spouses of patients with schizophrenia, which highlight the need for identification and support of spouses and other family members of patients with schizophrenia.…”
Section: Comparisons With Other Studiessupporting
confidence: 91%
“…Our findings support earlier reports of a long diagnostic pathway to schizophrenia with depressive and negative symptoms and cognitive deficits before the emergence of psychotic symptoms. [69][70][71][72] We also found increased use of somatic health care services at least 5 years before index date, which is in line with earlier Danish studies of increased use of primary care 73 and somatic diseases before first diagnosis of schizophrenia. 74 The same pattern of increased societal costs was identified among spouses of patients with schizophrenia, which highlight the need for identification and support of spouses and other family members of patients with schizophrenia.…”
Section: Comparisons With Other Studiessupporting
confidence: 91%
“…It has previously been found that psychotic symptoms are under-detected or diagnostically disregarded in clinical settings [10,86]. A recent study found that the presence of apparently 'neurotic' symptoms in first-episode psychosis resulted in a disregard of underlying psychotic psychopathology [39]. In this sample, a clinical focus on obsessive-compulsive symptomatology may have had similar consequences.…”
Section: Discussionmentioning
confidence: 71%
“…Unfortunately, psychotic symptoms are in the clinical setting often under-detected or even ignored when detected. A recent Norwegian study [ 46 ] found that the presence of apparently “neurotic” symptoms in the initial phases of schizophrenia resulted in a disregard of the underlying psychotic psychopathology. Such neurotic symptomatology may be more prevalent among help-seeking (vs. non-help-seeking) schizophrenia spectrum individuals [ 47 ].…”
Section: Discussionmentioning
confidence: 99%